Makna Simbolik Tari Panji Kahirupan di Kabupaten Cirebon - Dini Setiawati Putri; Sestri Indah Pebrianti (Jurnal Riset Rumpun Seni, Desain dan Media, 2025)
Panji Kahirupan Dance is a Cirebonese mask dance created by H. Taufik Hidayat, the founder of Sanggar Ki Bagus Rangin. This dance portrays the journey of human life, from pre-birth to adulthood, inspired by the changing characters (wanda) of the Cirebon mask tradition. This study aims to describe and analyze the symbolic meanings embedded in the Panji Kahirupan Dance. The research uses a qualitative method with a semiotic approach, allowing the researcher to explore both the denotative and connotative meanings of the symbolic elements in the dance. Data were collected through observation, interviews, and documentation, and validated using triangulation of techniques and sources. The data analysis involves data reduction to select relevant information, data presentation to synthesize findings, and conclusion drawing to interpret the symbolic meanings of each performance element. The costumes carry symbolic meanings through their colors: white represents the sanctity of life’s beginning, yellow symbolizes spirit, and red denotes ambition. The soft gamelan music contributes to a spiritual and contemplative atmosphere. The floor patterns, such as circles and straight lines, symbolize the life cycle and life’s purpose.